The effect of location of sound-absorbing materials in calculating the reverberation time of the hall by different formulas - Stauskis, Vytautas J. (Journal of Civil Engineering and Management, 2003)
Earlier formulas used for calculating the echoing length in a hall did not make allowance for the location of sound-absorbing materials and the shape of the hall. Fitzroy in 1959 and Neubauer in 1999 tried to take these factors into account. The echoing length calculations were made in a 1018 m3 hall where sound-absorbing materials were placed on the floor and the lateral walls. Formulas produced by 6 authors were used for calculations. As the echoing length is calculated by Fitzroy's and Neubauer's formulas, with the sound-absorbing materials of different acoustical properties placed on various planes of the hall, large differences in values are obtained compared with the calculations based on Eyring's formula. When a half of the floor area is covered with a sound-absorbing material, the increase of its absorption ratio results in the increase of the difference in echoing lengths calculated by Fitzroys' and Neubauer's formulas. When only the lateral walls are covered with sound-absorbing material, the increase of their absorption coefficient from 0,1 to 0,6 results in a 3 s (or three-fold) increase in the echoing length difference when calculated by Fitzroy's formula and in a 2 s (or two-fold) increase when calculated by Eyring's formula. Calculation by other formulas gives an insignificant difference of ∼0,5 s. As Fitzroy's and Neubauer's formulas are used, the difference becomes more significant: the larger the average hall absorption coefficient, the larger the difference.First Published Online: 26 Jul 2012